A high-efficiency heat-conducting new energy vehicle coolant and preparation method thereof

By adding suspension and other additives to the new energy vehicle coolant coolant coolant, and adjusting the pH value, the pH value is adjusted to solve the problem of low cooling efficiency and poor metal corrosion performance of the coolant. The effect of anti -corrosion.

CN115584249BActive Publication Date: 2025-01-28HEFEI HUAQING FANGXING SURFACING TECH CO LTD

Patent Information

Application Number
CN202211370032.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-03
Publication Date
2025-01-28
Estimated Expiration
2042-11-03

AI Technical Summary

Technical Problem

The heat transfer efficiency of new energy vehicle coolant is low and the metal anti-corrosion performance is poor.

Method used

A new energy vehicle coolant with high -efficiency thermal conductivity includes the suspension of the base solution, the sibidane aluminum aluminum aluminum aluminum aluminum aluminum aluminum aluminum, the foam, the corrosion agent, the rust -resistant agent, the stuffing agent, and the inhibitory additive. The pH value to 7.5-8.5 to improve performance.

Benefits of technology

It realizes high thermal conductivity, good metal corrosion resistance and anti -freezing performance, and is suitable for new energy vehicles and energy storage power stations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003967027170000041
    Figure GDA0003967027170000041
  • Figure GDA0003967027170000051
    Figure GDA0003967027170000051
Patent Text Reader

Abstract

The invention discloses a highly efficient heat-conductive new energy vehicle coolant and a preparation method thereof, wherein the components include a base liquid having a mass volume ratio of 500-1000 mL: 2-10 mL: 0.03-0.5 g: 5-10 g: 5-10 g: 0.02-0.1 g: 1-10 g, a suspension of silane-modified nano-alumina having a mass concentration of 1-5%, a defoamer, a corrosion inhibitor, a rust inhibitor, a scale inhibitor and an inhibitory additive, and the pH of the coolant is regulated to 7.5-8.5 by an alkali metal hydroxide. The formula system of the coolant of the present invention achieves the advantages of high thermal conductivity and good metal corrosion resistance based on the synergistic effect of each component, and can be used in the fields of new energy vehicles, energy storage power stations, etc. Therefore, it has a good prospect for application and promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of coolants, and in particular relates to a highly efficient heat-conducting new energy automobile coolant and a preparation method thereof. Background Art

[0002] With the improvement of my country's scientific and technological strength, many innovative technologies have been applied to new energy vehicles, providing more favorable conditions for the development of new energy vehicles. As the core component of new energy vehicle technology, the improvement of battery safety management technology has always been the focus of new technology breakthroughs that the industry pays the most attention to. The power source of new energy vehicles is batteries, which is completely different from fuel vehicles. The temperature range of the battery must be maintained at 20℃-35℃, and the coolant plays a vital role in it. In addition, the electronic control and motor will produce certain losses during the operation process. These losses are usually dissipated outward in the form of heat. Effective cooling media and cooling methods are also required to take away the heat to ensure that the electronic control and motor can operate safely and reliably in a stable cold and hot cycle balance state.

[0003] The temperature inside the battery is often too high due to untimely heat dissipation, which reduces the performance and shortens the life of the battery. Therefore, all batteries are equipped with a heat dissipation system. At present, most mainstream domestic manufacturers use liquid cooling technology and use coolant as the heat dissipation fluid medium. However, the technical difficulties encountered by the coolant of new energy vehicles are low heat transfer efficiency of the coolant and poor metal corrosion resistance. Summary of the invention

[0004] In view of the problems of low heat transfer efficiency and poor metal corrosion resistance of existing new energy vehicle coolants, the present invention provides a high-efficiency heat-conducting new energy vehicle coolant and a preparation method thereof, aiming to make it have excellent heat transfer, metal corrosion resistance, metal ion inhibition and other characteristics.

[0005] To achieve the purpose, the present invention adopts the following technical solution:

[0006] The invention firstly discloses a high-efficiency heat-conducting new energy automobile coolant, which is characterized in that: the components of the coolant include a base liquid with a mass volume ratio of 500-1000mL: 2-10mL: 0.03-0.5g: 5-10g: 5-10g: 0.02-0.1g: 1-10g, a suspension of silane-modified nano-alumina with a mass concentration of 1-5%, a defoamer, a corrosion inhibitor, a rust inhibitor, a scale inhibitor and an inhibitory additive, and the pH of the coolant is regulated to 7.5-8.5 by an alkali metal hydroxide.

[0007] Preferably, the base liquid is a mixture of ethylene glycol and propylene glycol in a volume ratio of 4:1.

[0008] Preferably, the suspension of the silane-modified nano-alumina is prepared by mixing ethylene glycol and water in a volume ratio of 1:1 and stirring evenly, adding a polyoxyalkylene oxide copolymer surfactant and continuing to stir evenly, and then adding the silane-modified nano-alumina and stirring evenly to obtain a nanofluid mixed solution; and ultrasonically treating the nanofluid mixed solution to obtain a suspension of the silane-modified nano-alumina. The polyoxyalkylene oxide copolymer surfactant accounts for 5% of the mass of the silane-modified nano-alumina.

[0009] Preferably, the inhibitor additive is a mixture of phenol inhibitors, sugar alcohol inhibitors and metal ion inhibitors. Wherein: the phenol inhibitor is preferably one or a mixture of 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol and 4,4-butylene-bis(3-methyl-6-tert-butylphenol). The sugar alcohol inhibitor is preferably one or a mixture of erythritol, xylitol, mannitol and maltitol. The metal ion inhibitor is preferably one or a mixture of 1,8-naphthalene dicarboxylic acid imide and sulfhydryl imidazole.

[0010] Preferably: the defoaming agent is dimethyl silicone oil or an emulsified polyether-modified silicone defoaming agent; the corrosion inhibitor is at least one of phenyltriazole, p-hydroxybenzoic acid and sodium benzoate; the rust inhibitor is at least one of sodium petroleum sulfonate and heptadecenyl imidazoline succinate; the scale inhibitor is at least one of hydroxyethylidene diphosphonic acid, sodium ethylenediaminetetramethylenephosphonic acid and aminotrimethylenephosphonic acid.

[0011] In addition, the present invention also provides a method for preparing the new energy vehicle coolant, which comprises the following steps:

[0012] Add the inhibitor additive to the base liquid and stir evenly at room temperature, then add the corrosion inhibitor and the rust inhibitor in turn and stir evenly at room temperature, then add the suspension of silane-modified nano-alumina and stir evenly at room temperature, then add the scale inhibitor and stir evenly at room temperature, then add alkali metal hydroxide to adjust the pH value of the solution to 7.5-8.5, finally add the defoaming agent and stir evenly at room temperature to obtain the new energy vehicle coolant.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0014] 1. The present invention provides a formula system for a new energy vehicle coolant. The formula has the advantages of high thermal conductivity, good metal corrosion resistance, and good antifreeze performance (freezing point at -38°C) based on the synergistic effect of each component, and can be used in the fields of new energy vehicles, energy storage power stations, etc. Therefore, it has a good prospect for application and promotion.

[0015] 2. A suspension of silane-modified nano-alumina is added to the formulation system of the present invention, and a polyoxyalkylene oxide copolymer surfactant is added to the suspension during preparation, which improves the dispersion of the silane-modified nano-alumina suspension and enables the suspension to significantly improve the thermal conductivity in the coolant system, so that the thermal conductivity of the coolant can reach 0.696 / (W / m·K).

[0016] 3. The composition of phenol inhibitors, sugar alcohol inhibitors and metal ion inhibitors is added to the formula system of the present invention, which overcomes the problem that the base liquid is easily oxidized into by-products such as alkyd acid and aldehyde acid, which corrode metal parts. The synergistic effect of the three makes the coolant have good corrosion inhibition effect on various metals such as copper, brass, steel (304), aluminum (3003) and cast aluminum materials. DETAILED DESCRIPTION

[0017] The present invention is described in detail below in conjunction with the embodiments to illustrate the features and advantages of the present invention. The following embodiments are not intended to limit the present invention, and the formulations compiled by professionals in the field based on the ideas and raw material ratios of the present invention also fall within the protection scope of the present invention.

[0018] The specific preparation method of the cooling liquid in the following embodiments is as follows:

[0019] Add the inhibitor additive to the base liquid and stir it at 800 rpm at room temperature for 1 hour, then add the corrosion inhibitor and the rust inhibitor in turn and stir it at 800 rpm at room temperature for 1 hour, then add the suspension of silane-modified nano-alumina and stir it at 1000 rpm at room temperature for 2 hours, then add the scale inhibitor and stir it at 800 rpm at room temperature for 1 hour, then add the alkali metal hydroxide to adjust the pH value of the solution to ≈8, finally add the defoamer and stir it at 800 rpm at room temperature for 1 hour, and obtain the new energy vehicle coolant.

[0020] The performance test method (or standard) of the cooling liquid obtained in the following examples is as follows:

[0021] Coolant thermal conductivity test method: Flash method for measuring thermal diffusivity or thermal conductivity GB / T 22588-2008

[0022] Metal anti-corrosion performance test method: Engine coolant corrosion test method (glassware method) SH / T 0085-91; Engine coolant corrosion test method for cast aluminum alloys under heat transfer state SH / T0620-95

[0023] 1. Comparison of the effects of silane-modified nano-alumina in coolants

[0024] Example 1

[0025] The components of the coolant configured in this embodiment include: 800 mL of ethylene glycol, 200 mL of propylene glycol, 10 mL of a suspension of silane-modified nano-alumina with a mass concentration of 2%, 0.5 g of an emulsified polyether-modified silicone defoamer (THIX-299), 2.5 g of phenyltriazole, 5 g of sodium benzoate, 2.5 g of sodium petroleum sulfonate, 2.5 g of heptadecenyl imidazoline alkenyl succinate, 0.02 g of hydroxyethylidene diphosphonic acid, 1.5 g of hydroxytyrosol, 1.5 g of erythritol, 1.0 g of 2,6-di-tert-butyl-4-ethylphenol, and 2.0 g of 1,8-naphthalimide, and the pH of the coolant is regulated to 8.0 by a potassium hydroxide solution with a mass fraction of 0.01-0.08%.

[0026] In this embodiment, the suspension of silane-modified nano-alumina is prepared according to the following method:

[0027] (1) Weigh 0.1g KH550, add 4g deionized water, and adjust the pH to ≈ 3 with acetic acid to fully dissolve KH550. Weigh 2g nano-Al2O3 particles with a particle size of 100nm in a 250mL round-bottom flask, add 100mL ethanol / water mixture (ethanol: water = 1:1, mass ratio) to the flask, and ultrasonically disperse for 1h to form a nano-Al2O3 dispersion. Add the hydrolyzate of KH550 to the nano-Al2O3 dispersion, heat and reflux at 80℃ with a constant temperature magnetic stirrer for 2h, centrifuge after the reaction is completed, wash with anhydrous ethanol 3 times to remove the KH550 not loaded on the Al2O3 surface, dry in an oven at 80℃ for 24h, and grind for use.

[0028] (2) First, 50 g of ethylene glycol and 50 g of water were mixed, and the mixture was stirred at a constant speed for 10 min using a magnetic stirrer to form a base liquid; 0.1 g of a polyoxyalkylene oxide copolymer surfactant (Silwet HS106) was added to the base liquid, and the mixture was stirred at a constant speed for 20 min using a magnetic stirrer; finally, 2 g of ground silane-modified nano-Al2O3 particles were added, and the mixture was stirred at a constant speed for 1 h using a magnetic stirrer to form a nanofluid mixture; the nanofluid mixture was subjected to ultrasonic treatment for 1 h to form a suspension of silane-modified nano-alumina.

[0029] Example 2

[0030] The components of the coolant prepared in this embodiment are different from those in Embodiment 1 only in that the amount of the suspension of silane-modified nano-alumina is 6 mL.

[0031] Example 3

[0032] The components of the coolant prepared in this embodiment are different from those in Embodiment 1 only in that the amount of the suspension of silane-modified nano-alumina is 2 mL.

[0033] Example 4

[0034] The components of the coolant prepared in this embodiment are different from those in Embodiment 1 only in that the amount of the suspension of silane-modified nano-alumina is 12 mL.

[0035] Comparative Example 1

[0036] The components of the coolant configured in this embodiment are different from those in Embodiment 1 only in that the amount of the suspension of silane-modified nano-alumina is 0.

[0037] Comparative Example 2

[0038] The components of the coolant prepared in this embodiment are the same as those in Embodiment 1, except that no polyoxyalkylene oxide copolymer surfactant is added when preparing the suspension of silane-modified nano-alumina.

[0039] Comparative Example 3

[0040] The components of the coolant configured in this embodiment are the same as those in Embodiment 1, the only difference being that the surfactant added when preparing the suspension of silane-modified nano-alumina is sodium dodecylbenzene sulfonate.

[0041] The thermal conductivity and metal corrosion resistance of the coolants configured in the above-mentioned embodiments and comparative examples are shown in Table 1.

[0042] Table 1 Coolant thermal conductivity and metal corrosion resistance test results

[0043]

[0044] By comparing the data of Examples 1 to 4 and Comparative Example 1, it can be seen that as the amount of the silane-modified nano-alumina suspension in the formulation system of the present invention increases, the thermal conductivity of the coolant of the present invention shows a trend of first increasing and then decreasing.

[0045] Comparative Example 1, Comparative Example 2 and Comparative Example 3 show that the polyoxyalkylene oxide copolymer surfactant (Silwet HS106) selected in the preparation process of the silane-modified nano-alumina suspension in the formulation system of the present invention helps to improve the thermal conductivity of the coolant of the present invention.

[0046] From the above, it can be seen that the addition of polyoxyalkylene oxide copolymer surfactant to the silane-modified nano-alumina suspension has a significant promoting effect on the improvement of thermal conductivity in the formulation system of the present invention. This is because the polyoxyalkylene oxide copolymer surfactant improves the stability and dispersibility of the silane-modified nano-alumina suspension, so that the suspension can play a role in significantly improving the thermal conductivity in the coolant system.

[0047] 2. Comparison of the effects of different inhibitor additives in coolants

[0048] Example 5

[0049] The components of the coolant configured in this embodiment include: 800 mL of ethylene glycol, 200 mL of propylene glycol, 10 mL of a suspension of silane-modified nano-alumina with a mass concentration of 2%, 0.5 g of an emulsified polyether-modified silicone defoamer (THIX-299), 2.5 g of phenyltriazole, 5 g of sodium benzoate, 2.5 g of sodium petroleum sulfonate, 2.5 g of heptadecenyl imidazoline alkenyl succinate, 0.02 g of hydroxyethylidene diphosphonic acid, 2.0 g of xylitol, 1.5 g of mannitol, 1.0 g of 4,4-butylene-bis(3-methyl-6-tert-butylphenol), and 2.0 g of 1,8-naphthalimide, and the pH of the coolant is regulated to 8.0 by potassium hydroxide.

[0050] Example 6

[0051] The components of the coolant configured in this embodiment are different from those in Embodiment 1 in that the content of 4,4-butylene-bis(3-methyl-6-tert-butylphenol) is 0.

[0052] Example 7

[0053] The components of the coolant configured in this embodiment are different from those in Embodiment 1 in that the content of 1,8-naphthalimide is 0.

[0054] Example 8

[0055] The components of the coolant configured in this embodiment are different from those in Embodiment 1 in that the contents of 4,4-butylene-bis(3-methyl-6-tert-butylphenol) and 1,8-naphthalimide are both 0.

[0056] Comparative Example 4

[0057] The components of the coolant prepared in this embodiment are different from those in Embodiment 1 in that the contents of xylitol, mannitol, 4,4-butylene-bis(3-methyl-6-tert-butylphenol) and 1,8-naphthalimide are all 0.

[0058] The thermal conductivity and metal corrosion resistance of the coolants configured in the above embodiments and comparative examples are shown in Table 2.

[0059] Table 2 Test results of coolant thermal conductivity and metal corrosion resistance

[0060]

[0061] By comparing Examples 5 to 8 with Comparative Example 4, it can be seen that the composition of phenol inhibitors, sugar alcohol inhibitors and metal ion inhibitors added to the formulation system of the present invention has a good corrosion inhibition effect on red copper, brass, steel (304), aluminum (3003) and cast aluminum materials. At the same time, there is a synergistic effect between the three, overcoming the problems of the base liquid being easily oxidized into by-products such as alkyd and aldehyde acid, which corrode metal parts and the precipitation of metal ions.

[0062] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0063] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A highly efficient heat-conducting new energy vehicle coolant, characterized by: The components of the coolant include a base liquid with a mass volume ratio of 500-1000 mL: 2-10 mL: 0.03-0.5 g: 5-10 g: 5-10 g: 0.02-0.1 g: 1-10 g, a suspension of silane-modified nano-alumina with a mass concentration of 1-5%, a defoamer, a corrosion inhibitor, a rust inhibitor, a scale inhibitor and an inhibitor additive, and the pH of the coolant is adjusted to 7.5-8.5 by an alkali metal hydroxide; The preparation method of the suspension of silane-modified nano-alumina is as follows: ethylene glycol and water are mixed in a volume ratio of 1:1 and stirred evenly, polyoxyalkylene oxide copolymer surfactant Silwet HS106 is added and stirred evenly, and then silane-modified nano-alumina is added and stirred evenly to obtain a nanofluid mixed liquid; the nanofluid mixed liquid is subjected to ultrasonic treatment to obtain a suspension of silane-modified nano-alumina; The inhibitor additive is a mixture of phenol inhibitors, sugar alcohol inhibitors and metal ion inhibitors.

2. The new energy vehicle coolant according to claim 1, characterized in that: The base liquid is a mixture of ethylene glycol and propylene glycol in a volume ratio of 4:

1.

3. The new energy vehicle coolant according to claim 1, characterized in that: The polyoxyalkylene oxide copolymer surfactant accounts for 5% of the mass of the silane-modified nano-alumina.

4. The new energy vehicle coolant according to claim 1, characterized in that: The phenol inhibitor is one or a mixture of 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol and 4,4-butylene-bis(3-methyl-6-tert-butylphenol).

5. The new energy vehicle coolant according to claim 1, characterized in that: The sugar alcohol inhibitor is one or a mixture of hydroxytyrosol, erythritol, xylitol, mannitol and maltitol.

6. The new energy vehicle coolant according to claim 1, characterized in that: The metal ion inhibitor is one or a mixture of 1,8-naphthalene diimide and sulfhydryl imidazole.

7. The new energy vehicle coolant according to claim 1, characterized in that: The defoaming agent is dimethyl silicone oil or an emulsified polyether modified silicone defoaming agent; the corrosion inhibitor is at least one of phenyltriazole, p-hydroxybenzoic acid and sodium benzoate; the rust inhibitor is at least one of sodium petroleum sulfonate and heptadecenyl imidazoline succinate; the scale inhibitor is at least one of hydroxyethylidene diphosphonic acid, sodium ethylenediaminetetramethylenephosphonic acid and aminotrimethylenephosphonic acid.

8. A method for preparing the new energy vehicle coolant according to any one of claims 1 to 7, characterized in that: The steps include: Add the inhibitor additive to the base liquid and stir evenly at room temperature, then add the corrosion inhibitor and the rust inhibitor in turn and stir evenly at room temperature, then add the suspension of silane-modified nano-alumina and stir evenly at room temperature, then add the scale inhibitor and stir evenly at room temperature, then add alkali metal hydroxide to adjust the pH value of the solution to 7.5-8.5, finally add the defoaming agent and stir evenly at room temperature to obtain the new energy vehicle coolant.

Citation Information

Patent Citations

  • Preparation method of efficient anti-corrosion cooling liquid additive and finished product

    CN114958312A

Cited By

  • A high-thermal-conductivity bacteriostatic new energy battery cooling liquid and a preparation method thereof

    CN120424624B